Results of dynamic monitoring of the spectrum of bacterial causes of acute urinary tract infections in children - Lezhenko, H. O.; Pashkova, O. Ye.; Samoylyk, K. V.; Леженко, Геннадій Олександрович; Пашкова, Олена Єгорівна; Самойлик, Катерина Валеріївна (Запорізький державний медичний університет, 2022)
The aim of the study: to explore in dynamics the structure of pathogens in children of Zaporizhzhia region with acute urinary tract infections and the possible changes in their antibiotic susceptibility. Materials and methods. We analysed results of urine culture in 439 children aged 4 to 18 years with acute urinary tract infection (293 patients in 2014–2016 and 146 patients in 2018–2020). Determination of bacterial species and susceptibility to antibiotics was performed on a bacteriological analyzer VITEK 2 COMPACT (bioMerieux, France) using AES software: Global CLSI-based + Phenotypic (2014, 2018) in accordance with CLSI and EUCAST tables. The coefficient of antibiotic resistance was additionally calculated for each isolate. Results. According to the analysis of bacteriological monitoring, it was found that in 2018–2020 compared to 2014–2016 among the causative agents of acute urinary tract infections in children, the role of gram-negative bacteria had raised due to increasing the proportion of Escherichia сoli and Proteus mirabilis. Gram-positive microflora has been represented by bacteria of the genus Enterococcus, in 2018–2020 in most samples was isolated Enterococcus faecium (28.1 %), in 2014–2016 among the representatives Enterococcus faecalis prevailed (38.9 %). Мета роботи – дослідити в динаміці структуру збудників гострих інфекцій сечовивідної системи у дітей Запорізької області та можливу зміну їхньої чутливості до антибіотиків. Матеріали та методи. Здійснили аналіз результатів бактеріологічних засівів сечі 439 дітей віком від 4 до 18 років, які хворі на гостру інфекцію сечовивідної системи (293 пацієнти за період 2014–2016 рр. та 146 пацієнтів за 2018–2020 рр.). Визначення видів та чутливості бактерій до антибіотиків здійснили на бактеріологічному аналізаторі VITEK 2 COMPACT (bioMerieux, Франція) з використанням програмного забезпечення AES: Global CLSI-based + Phenotypic (2014, 2018) відповідно до таблиць SLSI та EUCAST. Для кожного ізоляту додатково розраховували коефіцієнт резистентності до антибіотиків. Результати. Встановлено, що в 2018–2020 рр. порівняно з періодом 2014–2016 рр. серед збудників гострих інфекцій сечовивідної системи у дітей зросла роль грамнегативних бактерій внаслідок збільшення питомої ваги Escherichia сoli та Proteus mirabilis. Грампозитивна мікрофлора представлена бактеріями роду Enterococcus, серед них у 2018–2020 рр. переважав Enterococcus faecium (28,1 %), а в 2014–2016 рр. в більшості проб виділяли Enterococcus faecalis (38,9 %).
Результати динамічного моніторингу спектра бактеріальних збудників гострих інфекцій сечовивідної системи у дітей
Lezhenko H. O. - ORCID ID: 0000-0003-0851-4586; Pashkova O. Ye. - ORCID ID: 0000-0002-3935-5103; Samoylyk K. V. -ORCID ID: 0000-0003-3226-1785.
Keywords: children; urinary tract infections; antibiotic resistance; діти; інфекції сечовивідної системи; антибіотикорезистентність